Optimization of photo-polymerized sol gel monolithic stationary phases prepared in polyacrylate-coated fused-silica capillaries for capillary electrochromatography - Simas Vaz, Fernando Antonio; Moutinho, Arthur Damasio; Rodrigues Furtado de Mendonca, Jose Paulo; de Araujo, Ricardo Tavares [UNESP]; Lima Ribeiro, Sidney Jose [UNESP]; Polachini, Ferminio Cesar [UNESP]; Messaddeq, Younes [UNESP]; Leal de Oliveira, Marcone Augusto (Elsevier B.V., 2012)
The preparation of photo-polymerized sol-gel monolithic stationary phases (MSP) within 100 mu m internal diameter polyacrylate-coated fused-silica capillaries for use in capillary electrochromatography (CEC) was optimized. Eight mixtures containing different amounts of methacryloxypropyltrimethoxysilane (MPTMS) as the polymeric precursor, hydrochloric acid solution as the catalyst, toluene as the porogen and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Irgacure 819) as the photo-initiator were irradiated at 370 nm inside the capillaries in order to complete the MSP polymerization, according to a fractional factorial experimental design 2(IV)(4-1). All the preparation procedure, from capillary pretreatment until the MSP is ready to use in CEC, were made in less than four hours in mild conditions. A high pressurization injection device (HPID) useful for micro-volume syringes was built in order to achieve practical, controlled and precise injections of sols, solvents and electrolytes in the capillaries. The eight MSP were equally washed, conditioned and submitted to CEC procedures via short-end injection, which showed higher efficiency and peak height taking shorter analysis time. Electrochromatographic behaviors of the MSP were corroborated with morphological characterizations by scanning electron microscopy. The optimum condition, which allowed the separation of standard mixture containing thiourea (marker compound), naphthalene, acenaphthene, fluorene, phenanthrene and anthracene in twelve minutes without external pressure assistance, showed efficiencies up to 51,460 N/m, relative standard deviation from 0.05 to 3.3% for migration/retention time and from 0.14 to 1.6% for relative area (considering thiourea as an internal standard) and also showed no statistical evidence that three MSP prepared at the same condition are different within 95% confidence interval. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Capillary electrochromatography; Monolithic stationary phase; Short-end injection; Polycyclic aromatic hydrocarbons; Polyacrylate-coating fused-silica capillary